Вплив кліматичних зон Ірану на проектування торгово-розважальних комплексів - Слєпцов, О. С.; Солтані, А. А.; Sleptsov, O.; Soltani, A. A. (Видавництво Львівської політехніки, 2019)
У статті розглянуто основні кліматичні зони Ірану та їх вплив на формування архітектури торгово-розважальних комплексів і дизайн інтер’єру сучасних торгових приміщень. Також у роботі висвітлено питання формування різних функціональних блоків, об’єднаних в єдину модель ТРК. У разі порівняно стандартного зовнішнього об’ємно-просторового вирішення, внутрішнє оздоблення часто виконують під впливом національних традицій і культурно-релігійних особливостей країни.

The article discusses main climatic zones of Iran and their impact on the architecture formation of shopping and entertainment complexes and the interior design of contemporary commercial premises. Also this article consider formation issues of the various functional blocks, united in a single model of SEC. Shopping and entertainment complexes have become widespread in the United States and gradually being developed and built all around the world. However, each country has its own specifics for the creation and development of such buildings. There is a need to take into account local and national traditions of architectural forming to combine them with a new ultimate construction technologies of shopping and entertainment complexes in the East countries, especially in such as Iran. With a relatively standard external spatial solution, the interior decoration is often getting under influence of the national traditions, cultural and religious characteristics of the country. Modern shopping and entertainment complexes are important cultural and social centers of modern Iranian cities and their role in the life of society is constantly increasing. publications analysis of domestic and foreign experience in the design of SEC and literary sources suggests that this type of buildings constantly requires updating the scientific and methodological base and recommendations for their design, taking into account various factors and conditions. The purpose of the article is an analysis of the SEC growth in Iran and the development of recommendations relating to their functional-planning and spatial organization associated with the characteristics of country zoning (design, construction and climatic zones). The purpose of the research led to the study of main factors influencing the shaping of the main functional units and the entire Shopping and entertainment complex, as well as the development of nomenclature recommendations for the most diverse types of SEC for the conditions of Iran. This author’s research is aimed at developing recommendations related to the new construction of Shopping and entertainment centers, however, some cases concerning industrial enterprises’ reconstruction with the modernization and renovation for the SEC functions are also included in the author’s sphere of interest. Such cases exist in the designing practice and require special attention while developing their internal structures and general plans for the site. Particular attention should be paid to the new construction of Shopping and Entertainment complexes in the open suburban spaces of free areas in residential neighborhoods. This is the most promising subtype of shopping and entertainment complexes aimed at systematic development of urban areas, taking into account the requirements of the city’s master plan.
The influence of iran's climatic zones on design of trade-related complexes
Keywords: торгово-розважальні комплекси (ТРК); кліматична зона; функціональнопланувальна структура; Іран; shopping and entertainment complexes (SEC); climatic zone; functional and planning structure; Iran; 72.012; 721